Navigating Tumultuous Change in the Medical Profession: The Coalition for Physician Accountability. (August 2019) - Chaudhry, Humayun J.; Kirch, Darrell G.; Nasca, Thomas J.; Katsufrakis, Peter J.; McMahon, Graham T.; Shannon, Stephen C.; Ciccone, Andrea L.
Abstract : Collaboration among the national organizations responsible for self-regulation in medicine in the United States is critical, as achieving the quadruple aim of enhancing the patient experience and improving population health while lowering costs and improving the work life of clinicians and staff is becoming more challenging. The leaders of the national organizations responsible for accreditation, assessment, licensure, and certification recognize this and have come together as the Coalition for Physician Accountability. The coalition, which meets twice per year, was created in 2011 as a discursive space for group discussion and action related to advancing health care, promoting professional accountability, and improving the education, training, and assessment of physicians. The coalition offers a useful avenue for members to seek common ground and develop constructive, thoughtful solutions to common challenges. Its members have endorsed consensus statements about current topics relevant to health care regulation, advanced innovation in medical school curricula, encouraged a plan for single graduate medical education accreditation for physicians holding MD and DO degrees, supported interprofessional education, championed opioid epidemic mitigation strategies, and supported initiatives responsive to physician workforce shortages, including the Interstate Medical Licensure Compact, an expedited pathway by which eligible physicians may be licensed to practice in multiple jurisdictions.